Nodular localized primary cutaneous amyloidosis: a bullous variant. (April 2014) - LaChance, A.; Phelps, A.; Finch, J.; Lu, J.; Elaba, Z.; Rezuke, W.; Murphy, M. J.
Summary Primary cutaneous amyloidosis describes a group of disorders in which amyloid is deposited in the skin without evidence of systemic involvement. Nodular localized primary cutaneous amyloidosis (NLPCA) is a rare form of these skin‐restricted amyloidoses. We present an unusual case of NLPCA in a 51‐year‐old man, who had clinical and histopathological evidence of subepidermal bullous formation, a unique feature in NLPCA. The possible pathogenesis of this change is discussed.